Can We Change the Functionality of HDL Cholesterol with Nonpharmacological and Pharmacological Agents? - Dragan, S.; Serban, C.; Banach, M. (Current Medicinal Chemistry, 2014)
Many pharmacological and non-pharmacological strategies have been used to increase high-density lipoprotein- cholesterol (HDL-C) levels, but the results obtained have not been consistently associated with effective cardiovascular risk reduction. Therefore, research is now focused to improve HDL functionality, independent of HDL-C levels. The quality of HDL particles can vary considerably due to its heterogeneity caused by various lipids, proteins, vitamins, hormones and small RNAs that are associated with HDL. These components could act as potential HDL-related biomarkers, which may guide effective therapeutic interventions. Evaluation of HDL functionality seems to be more relevant, given the current evidence of the pleiotropic potentially atheroprotective functions of HDL. It is relevant to understand which HDL-related properties involved in its cardioprotective functions, in order to develop pharmacological and nonpharmacological therapies to improve HDL functionality.
Keywords: reverse cholesterol transport